2009
DOI: 10.4141/cjps08150
|View full text |Cite
|
Sign up to set email alerts
|

Management of wild oat (Avena fatua L.) in tame oat (Avena sativa L.) with early seeding dates and high seeding rates

Abstract: wild oat (Avena fatua L.) in tame oat (Avena sativa L.) with early seeding dates and high seeding rates. Can. J. Plant Sci. 89: 763Á773. Traditionally, farmers have delayed seeding to manage wild oat (Avena fatua L.) in tame oat (Avena sativa L.) crops, but this practice can adversely affect grain yield and quality. The objectives of this study were: (1) to evaluate the effectiveness of using high seeding rates with early-seeded oat to maintain grain yield and quality, and (2) to determine an optimum seeding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 11 publications
8
19
0
Order By: Relevance
“…This indicates that annual canarygrass could not produce enough tillers at the lower seeding rates to completely compensate for the lower plant densities at the lower seeding rates. Similar results have been found in oat (May et al 2009b), common wheat and barley (Lafond 1994). The individual site intercepts ranged from 431 to 142 panicles m (2 , but on an individual basis none of the site intercepts significantly deviated from the overall intercept (Fig.…”
Section: Seeding Ratesupporting
confidence: 83%
See 3 more Smart Citations
“…This indicates that annual canarygrass could not produce enough tillers at the lower seeding rates to completely compensate for the lower plant densities at the lower seeding rates. Similar results have been found in oat (May et al 2009b), common wheat and barley (Lafond 1994). The individual site intercepts ranged from 431 to 142 panicles m (2 , but on an individual basis none of the site intercepts significantly deviated from the overall intercept (Fig.…”
Section: Seeding Ratesupporting
confidence: 83%
“…Holt (1989) also found that seeding rate had no effect on the kernel weight of annual canarygrass. A similar response was observed in oat (May et al 2009b); however, a significant decrease in kernel weight from increasing the seeding rate has been found in common wheat and barley (Lafond 1994;O'Donovan et al 2012). The intercept was 6.8 g 1000 kernels…”
Section: Seeding Ratesupporting
confidence: 77%
See 2 more Smart Citations
“…Similarly, Castagna et al (1996) found a significant effect of the seeding rate on the number of grains per spike of winter spelt, which consisted in decreasing from 25.2 to 20.4 grains per spike between 200 and 400 grains m (2 . This phenomenon was also observed with oats (May et al 2009), where increasing the seeding rate (150, 250, 350 and 450 grains m (2 ) increased the plant density and spike density, but reduced the number of grains per panicle and the number of panicles per plant; the 1000-grain weight was not influenced by the seeding rate. These results highlight the theory of Grafius (1972), which suggests that plants compete for fixed resources during their development and that yield is the result of a balance among yield components.…”
Section: Effect Of Seeding Ratesupporting
confidence: 60%